Purification of glutathione S-transferase (GST) using mixed mode chromatography - M., Sivapragasam; Abdullah, Norhafizah (ESRSA Publications, 2014)
A simple and small scale laboratory method to compare between ultrasonication, glass bead shaking and chemical lysis were evaluated for the release of recombinant Glutathione S-Transferase (GST) from Escherichia coli. Since the protein Glutathione S-Transferase is expressed intracellularly, cell disruption process is the precursor step for protein recovery.GST was purified using assessment with PPA and HEA HyperCel resin. Optimum release of GST was via ultrasonication, 70% amplitude size with enzyme release of 129.9 U/mL. Purification yields via PPA HyperCel yielded 96% recovery while purification using HEA HyperCel yielded a 93% enzyme recovery.